Peran Pemerintah Daerah dalam Mengentaskan Kemiskinan Ekstrim di Kabupaten Karawang - Muhammad Farhan Fathurohman; Usep Dayat; Rachmat Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to identify and examine the role of local governments in alleviating extreme poverty zones in Karawang Regency. The theory used in this study is the role of government according to Siagian in Kuncoro (2004) which has four dimensional variables, including entrepreneurship, facilities, stimulus and coordinator. This study uses a qualitative descriptive method with data collection obtained through three ways or triangulation Sugiyono (2017), including interviews, observations and documentation studies, then the data is analyzed through the concept of Milles and Huberman (1982), which includes reduction, presentation and drawing conclusions. The results and discussion show that the role of the Karawang local government in alleviating extreme poverty which is reviewed through four dimensions is not optimal, where from the variable the role of entrepreneurs is still minimal work for the indigenous people of Karawang, the variable role of the coordinator is that there is no seriousness of the Karawang Regional Government in building good tourist destinations, the variable role of government facilities is also not considered optimal considering that there is still estrangement between the private sector and the community and the apathy shown by the local government of Karawang over the disintegrity problem, then the last variable of the role of the stimulus of the local government of Karawang only provides Karawang people who are in extreme poverty zones in the form of assistance. which is temporary and creates community dependence, not like assistance that can actually make the extreme poor of Karawang develop more advanced, such as communication training and entrepreneurship